Key Gaps in Models' Physical Representation of Climate Intervention and Its Impacts - Eastham, Sebastian D.; Butler, Amy H.; Doherty, Sarah J.; Gasparini, Blaž; Tilmes, Simone; Bednarz, Ewa M.; Burkhardt, Ulrike; Chiodo, Gabriel; Cziczo, Daniel J.; Diamond, Michael S.; Keith, David W.; Leisner, Thomas; et al. (Journal of advances in modeling earth systems, 2025)
Solar radiation modification (SRM) is increasingly discussed as a potential method to ameliorate some negative effects of climate change. However, unquantified uncertainties in physical and environmental impacts of SRM impede informed debate and decision making. Some uncertainties are due to lack of understanding of processes determining atmospheric effects of SRM and/or a lag in development of their representation in models, meaning even high‐quality model intercomparisons will not necessarily reveal or address them. Although climate models at multiple scales are advancing in complexity, there are specific areas of uncertainty where additional model development (often requiring new observations) could significantly advance understanding of SRM's effects, and improve our ability to assess and weigh potential risks against those of choosing to not use SRM. We convene expert panels in the areas of atmospheric science most critical to understanding the three most widely discussed forms of SRM. Each identifies three key modeling gaps relevant to either stratospheric aerosols, cirrus, or low‐altitude marine clouds. Within each area, key challenges remain in capturing impacts due to complex interactions in aerosol physics, atmospheric chemistry/dynamics, and aerosol‐cloud interactions. Across all three, in addition to arguing for more observations, the panels argue that model development work to either leverage different capabilities of existing models, bridge scales across which relevant processes operate, or address known modeling gaps could advance understanding. By focusing on these knowledge gaps we believe the modeling community could advance understanding of SRM's physical risks and potential benefits, allowing better‐informed decision‐making about whether and how to use SRM. Plain Language Summary Solar radiation modification has been suggested as a potential method to reduce climate warming and its associated impacts, with three different types the subject of most research: stratospheric aerosol injection; marine cloud brightening; and cirrus cloud thinning. However, while modeling studies suggest some such methods could be effective, key challenges remain in accurately simulating their impacts due to complex interactions in aerosol physics, atmospheric chemistry, atmospheric dynamics, and aerosol‐cloud interactions that are inherent to the three SRM methods. We highlight critical research gaps that must be addressed to improve solar radiation modification modeling, including uncertainties in aerosol‐cloud interactions, aerosol microphysics, and their global effects. These gaps, identified by expert panels through the Geoengineering Modeling Research Consortium, emphasize the need for more detailed laboratory and field studies, along with improved models at multiple scales. We specifically outline where additional fundamental research is needed to support decision making around SRM, which will inevitably be made under uncertainty. Key Points Agreement across models in the physical responses to solar radiation modification may not reflect high accuracy We identify nine key knowledge/modeling gaps where advances would improve understanding of solar radiation modification's physical impacts More observations are needed to constrain atmospheric processes uniquely affected by implementation of solar radiation modification